Subtypes of Antiphospholipid Antibodies in Neurologic Disorders: An Observational Study - Sahebari, Maryam; Rastin, Maryam; Boostani, Reza; Forughipour, Mohsen; Hashemzadeh, Kamila; Sadeghi, Samira H. (Current Rheumatology Reviews, 2019)
Background and Objectives: Concomitant neurologic manifestations and positive antiphospholipid antibodies (APAs) have been investigated in different manners. The present study aimed to investigate the association between neurologic manifestations and APAs. Materials and Methods: This cross-sectional descriptive study was conducted on 100 consecutive patients with selected neurological manifestations and at least one positive APAs within the age range of 20-50 years, referred to the Rheumatic Diseases Research Center from the Northeast Central Neurology Department of Iran during August 2012 to March 2014. Results: According to the results, 89% of the participants were persistently positive for APAs, including lupus anticoagulant, IgG anticardiolipin (aCL), IgM aCL, IgG β-2 glycoprotein 1 (β2- GP1), and IgM β2-GP1, observed in 16%, 41%, 42%, 17%, and 15% of the patients, respectively. Furthermore, 10% of the patients had concomitant lupus manifestations, and 37% of them showed anti-DNA. The IgG and IgM aCL were the most prevalent antibodies. Cerebral vascular accident (33%), retinal artery/vein occlusion (21%), and seizure (20%) were the most frequent presentations among the patients. In addition, the patients with multiple sclerosis (composing 3% of the subjects) were 100% positive for IgG and IgM aCL, as well as lupus anticoagulant. In addition, IgM anti-β2- GP1 was 100% positive in optic neuritis patients (composing 5% of the subjects) and was significantly associated with this neurologic disorder. IgM anti-β2-GP1 was also prevalent in the cases with Guillain-Barré syndrome. The most prevalent persistently positive antibody in the patients with cerebrovascular accident was IgM aCL. Conclusion: The findings of this study revealed some associations between the subtypes of APAs and incidence of neurologic disorders. However, the exact correlation between those symptoms and APAs needs further investigations.
Keywords: neurological accident